Efektivitas Media Sosial Instagram Sebagai Alat Penyuluhan Pajak untuk Meningkatkan Kepatuhan Wajib Pajak - Soadiking, Misbar; Muh.Akbar,; Muhammad Farid ,; A.Muhammad Syafar, (Jurnal Dakwah Tabligh, 2024)
This study evaluates the effectiveness of Instagram as a tax counseling medium in increasing taxpayer compliance. As an interactive visual platform, Instagram offers the convenience of conveying information that is interesting and easy to understand. This study uses a survey method with respondents from taxpayers who follow the official Instagram account of KPP Pratama Makassar Barat. The variables analyzed included the level of taxpayer compliance before and after exposure to counseling content, as well as the level of user engagement through the likes, comments, and question and answer sessions. The results of the study show that the use of Instagram has a positive and significant effect on improving compliance, especially in terms of timely reporting and tax payments. Educational content packaged in infographics and short videos has proven to be effective in attracting interest and encouraging understanding of taxpayers. User involvement through direct interaction also supports the achievement of tax education goals. The recommendations of this study emphasize the importance of optimizing relevant and easy-to-understand content to drive tax compliance through social media.Keywords: Effectiveness, Instagram, tax counseling, taxpayer compliance